Assessing Mean Glandular Dose in Mammography in Jordan According to American College of Radiology (ACR) Standards - Al Hrout R; Ayasrah M; Noor Azman NZ (Cancer Management and Research)
Rasha Al Hrout,1,2 Mohammad Ayasrah,3 Nurul Zahirah Noor Azman2 1Medical Radiologic Technologies, College of Allied Medical Sciences, Zarqa University, Zarqa, 13132, Jordan; 2School of Physics, Universiti Sains Malaysia, Penang, 11800 Gelugor, Malaysia; 3Department of Allied Medical Sciences, Faculty of Applied Medical Science, Jordan University of Science and Technology, Irbid, 22110, JordanCorrespondence: Nurul Zahirah Noor Azman, School of Physics, Universiti Sains Malaysia, Gelugor, Pulau Pinang, 11800 Gelugor, Malaysia, Tel +604 653 3668, Email nzahirah@usm.my Mohammad Ayasrah, Department of Allied Medical Sciences Faculty of Applied Medical Sciences, Jordan University of Science and Technology, P.O. Box 3030, Irbid, 22110, Jordan, Tel +96227201000-26939, Fax +96227201087, Email maayasrah@just.edu.joIntroduction: Breast cancer is a significant worldwide health issue, particularly in Jordan, where early detection via mammography is essential for effective disease management. Despite the little radiation risk associated with mammography, it is crucial to monitor radiation exposure to guarantee patient safety. This study intends to assess skin entrance exposure and compute the Mean Glandular Dose (MGD) in mammography units to determine adherence to established criteria and pinpoint areas for enhancement.Methods: To assess MGD, the study utilized the American College of Radiologists (ACR) phantom alongside a RaySafe X2 MAM dosimeter. Measurements of entrance kerma and half-value layer (HVL) were taken across 25 mammography units in Jordan. The MGD was calculated according to the ACR’s 2018 protocol, which provides a standardized approach to ensure accurate and comparable dose estimations. These measurements were then analyzed against the ACR’s threshold of 3 mGy to assess compliance.Results: The study found that the average MGD across all units was 2.3 mGy, with individual values ranging from 0.95 to 4.10 mGy. Although 67% of the units maintained MGD values within the ACR threshold, 33% exceeded the recommended limit of 3 mGy. Higher MGD values were particularly common in non-accredited facilities, where the average MGD reached 2.7 mGy, compared to 1.6 mGy in accredited units, suggesting gaps in quality control and adherence to best practices in non-accredited centers.Conclusion: This study emphasizes the critical role of accreditation and adherence to quality standards in maintaining safe and effective mammography practices. While most mammography units in Jordan meet the ACR’s recommended MGD limits, the elevated dose levels in some non-accredited facilities highlight the need for more rigorous implementation of accreditation standards. Improving compliance with established guidelines will enhance breast cancer screening effectiveness, ultimately supporting better early detection and outcomes for breast cancer in Jordan.Keywords: patient safety in cancer imaging, mammography quality assurance, mean glandular dose, healthcare accreditation, breast cancer screening, patient safety in cancer imaging, radiation dose optimization in cancer screening